Fixed drug eruptions to ciprofloxacin - a case report - Bhosale, Rama R.; Patil, Abhishek V. (International Journal of Basic & Clinical Pharmacology, 2017)
Fixed drug eruptions (FDE) are common adverse drug reactions and they recur at the same site with each exposure to a particular drug. Drugs inducing FDE are usually those taken intermittently. Most common drugs causing fixed drug eruptions are antibiotics and analgesics. Here, we report a case of FDE to ciprofloxacin which was used in treatment of upper respiratory tract infection.